Content Knowledge of Elementary School Teachers in Mathematics - PONNUSAMY, P. (THE PRIMARY TEACHER, 2014)
The basic aim of Mathematics education is to develop logical reasoning and problem solving capacity. To make the best teaching and learning processes in the classroom at school, content knowledge of the teacher in Mathematics is an important aspect. In this context, the present study was undertaken by the investigator. Main finding of the study reveals that the elementary school teachers kane good content knowledge in Mathematics